Policy actors or objects of policy? Teacher candidates' interpretations of 'teacher quality' policy initiatives in Australia. (October 2021) - Barnes, Melissa
Abstract: While it is acknowledged that teachers play an important role in negotiating education policy, there is limited research exploring how teacher candidates understand and engage in their roles as policy actors, particularly when they are the objects of these policies. With heightened emphasis on teacher quality and classroom readiness in policy initiatives globally, this paper interrogates how 135 final-year teacher candidates in an Australian university interpret recent teacher education policy reform measures that attempt to solve Australia's teacher quality problem. The findings suggest that these policy measures act as just another hurdle and reinforce deficit views about the profession. Highlights: Teacher candidates are positioned as receivers and objects of education policy. Teacher candidates view policy initiatives as hurdles in the fight for legitimacy. Teacher quality policies reinforce deficit views about teachers and the profession. Teacher candidates acknowledge that they are framed as the problem with education.